Studi Perhitungan Relay Jarak pada Saluran Double Circuit dengan Single Conductor antara Gi Kapal - Gi Pemecutan Kelod Menggunakan Artificial Neural Network (Ann) - Hadianto, Alfian; Arjana, I Gede Dyana; Setiawan, Widyadi (Majalah Ilmiah Teknologi Elektro, 2016)
The use of distance relays in the system SUTT 150 kV network, is expected to help the reliability of the transmission system. Setting the value of the distance relay network systems SUTT 150 kV substation Ship - GI Pemecutan kelod specified by PLN, akandilakukan research to obtain the new distance relay settings. Value setting relays within the network system SUTT 150 kV substation Ship - GI Pemecutan kelod: Zone 1: (R = 0.977, X = 2.684, Z = 2.86), Zone 2: (R = 1.341, X = 3684, Z = 3.92) , zone 3: (R = 2,107, X = 5789, Z = 6.16). Methods used to determine the return value of the distance relay settings for securing network systems SUTT 150 kV substation Ship - GI Pemecutan kelod is a method of Artificial Neural Network. Application of the method backpropagation Artificial Neural Network is used to determine the value of setting relays within the network system SUTT 150 kV substation Ship - GI Pemecutan kelod obtained from the method of Artificial Neural Network is zone 1 (R = 0.9911, X = 2.6886, Z = 2.86), zone 2: (R = 1.3313, X = 3.6798, Z = 3.92), zone 3: (R = 2.1251, X = 2.0995, Z = 6.16). Percentage difference ie, zone 1 (R = 0.0144%, X = 0.0017%, Z = 0.0000%), Zone 2: (R = 0.3626%, X = 0.3710%, Z = 0.3706%), Zone 3: (R = 1.1751%, X = 1.1562%, Z = 1.1538%).
Keywords: Rele Jarak, Gangguan Hubung Singkat, Artificial Neural Network, Setting Rele Jarak.